Species delimitation of newly collected spiders of the genus Pseudopoda (Araneae, Sparassidae) from Honghe Hani and Yi Autonomous Prefecture, Yunnan, China: An integrated morphological and molecular approach - Jianshuang Zhang; Tianqin Pan; He Zhang; Yuanqian Xing; Hao Yu; Yang Zhong (Zoosystematics and Evolution)
A further study of the spider genus Pseudopoda Jäger, 2000, from Honghe Hani and Yi Autonomous Prefecture, Yunnan, southwest China, is presented. A total of six species are here addressed based on morphology and five methods of molecular species delimitation, increasing the number of known species of the genus in this area from 10 to 13. They comprise three new species, namely P. xiaozhua J. Zhang, H. Yu & Y. Zhong, sp. nov. (♂♀), P. yangae J. Zhang, H. Zhang & Y. Zhong, sp. nov. (♂♀), and P. ying J. Zhang, H. Zhang & Y. Zhong, sp. nov. (♂), and three known species: P. huanglianensis Zhang, Jäger & Liu, 2023, P. mamillaris Zhang, Jäger & Liu, 2023, and P. oliviformis Zhang, Jäger & Liu, 2023. The males of the three known species are described for the first time. Detailed descriptions, diagnoses, photographs of the six species, and a distribution map for all 13 Pseudopoda species in Honghe Prefecture are provided. The DNA barcodes of the six species were obtained for species delimitation, sex matching, and future use.